2021
DOI: 10.3390/ijerph18063044
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of a Polyphenol Botanical Blend on Sleep and Daytime Functioning

Abstract: Despite the high prevalence of subclinical sleep disturbances, existing treatments are either potent prescription medications or over-the-counter supplements with minimal scientific support and numerous side effects. However, preliminary evidence shows that polyphenols such as rosmarinic acid and epigallocatechin gallate can support healthy sleep without significant side effects. Therefore, the present study examined whether a polyphenol botanical blend (PBB) could improve sleep and/or daytime functioning in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Experimental and observational studies on the relationship between dietary polyphenols and sleep are scarce [ 19 , 22 , 23 , 52 , 53 , 54 ]. So far, only three observational [ 19 , 22 , 54 ] and two experimental studies [ 23 , 52 ] have been found to relate polyphenol intake with sleep quality. This study proposed that participants who consume higher amounts of polyphenols are independently protected by 76% from poor sleep.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental and observational studies on the relationship between dietary polyphenols and sleep are scarce [ 19 , 22 , 23 , 52 , 53 , 54 ]. So far, only three observational [ 19 , 22 , 54 ] and two experimental studies [ 23 , 52 ] have been found to relate polyphenol intake with sleep quality. This study proposed that participants who consume higher amounts of polyphenols are independently protected by 76% from poor sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, a recent Italian observational study presented that higher consumption of certain dietary polyphenols (some subclasses of flavonoid, phenolic acids, and lignans) could enhance the sleep quality in healthy adults with normal body weight, but the association has not been confirmed among overweight/obese participants [ 19 ]. An RCT investigated the effect of 30-day polyphenol supplementation on sleep quality in participants with subclinical sleep disturbances [ 23 ]. In the study, polyphenol supplementation significantly improved sleep quality (β = 0.11; CI 95% 0.01, 0.22; p = 0.008) and decreased the insomnia severity index (β = −0.1; CI 95% −2.0, −0.03; p = 0.044) compared to the placebo group [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations